The Effect of Perioperative E-Health Interventions on the Postoperative Course: A Systematic Review of Randomised and Non-Randomised Controlled Trials. - Eva van der Meij; Johannes R Anema; René H J Otten; Judith A F Huirne; Frederieke G Schaafsma (PLoS ONE, 2016)
Background E-health interventions have become increasingly popular, including in perioperative care. The objective of this study was to evaluate the effect of perioperative e-health interventions on the postoperative course. Methods We conducted a systematic review and searched for relevant articles in the PUBMED, EMBASE, CINAHL and COCHRANE databases. Controlled trials written in English, with participants of 18 years and older who underwent any type of surgery and which evaluated any type of e-health intervention by reporting patient-related outcome measures focusing on the period after surgery, were included. Data of all included studies were extracted and study quality was assessed by using the Downs and Black scoring system. Findings A total of 33 articles were included, reporting on 27 unique studies. Most studies were judged as having a medium risk of bias (n = 13), 11 as a low risk of bias, and three as high risk of bias studies. Most studies included patients undergoing cardiac (n = 9) or orthopedic surgery (n = 7). All studies focused on replacing (n = 11) or complementing (n = 15) perioperative usual care with some form of care via ICT; one study evaluated both type of interventions. Interventions consisted of an educational or supportive website, telemonitoring, telerehabilitation or teleconsultation. All studies measured patient-related outcomes focusing on the physical, the mental or the general component of recovery. 11 studies (40.7%) reported outcome measures related to the effectiveness of the intervention in terms of health care usage and costs. 25 studies (92.6%) reported at least an equal (n = 8) or positive (n = 17) effect of the e-health intervention compared to usual care. In two studies (7.4%) a positive effect on any outcome was found in favour of the control group. Conclusion Based on this systematic review we conclude that in the majority of the studies e-health leads to similar or improved clinical patient-related outcomes compared to only face to face perioperative care for patients who have undergone various forms of surgery. However, due to the low or moderate quality of many studies, the results should be interpreted with caution.